Encouraging Purchases Through Stories: The Effectiveness of Word of Mouth in the Digital Era - Chamid, Abdul; Wibowo, Bambang Sri (LPPPIPublishing, 2025)
This study aims to explore the influence of Word of Mouth (WOM) on the purchase decision of Sinom-Tap products. Using a qualitative approach, the study involved in-depth interviews with five purposively selected customers, based on their experience with the product. The findings show that positive customer experiences have a significant impact in shaping recommendations, where recommendations from friends and family are much more trusted than commercial advertisements. Social media plays an important role in accelerating the spread of WOM and increasing the credibility of recommendations. The limitation of this study lies in the relatively small number of respondents, so generalisation of the findings may be limited. Nevertheless, this study makes an important contribution to the marketing literature by highlighting the dynamics of WOM in the context of health products in Indonesia, which remains under-explored. The originality of this study lies in its holistic analysis of the factors that influence WOM effectiveness, including speaker characteristics, topics discussed, and communication tools used, as well as important implications for marketing strategies in the digital era. The findings are expected to provide useful insights for marketers in optimally utilising WOM to increase loyalty and sales growth.